Suco de xique-xique (Pilosocereus gounellei): caracterização e avaliação in vitro do potencial prebiótico frente à Lactobacillus spp. - Ribeiro, Thais Santana (2019)
The xique-xique (Pilosocereus gounellei) is a species of cactus endemic to the northeastern region of Brazil. It is a natural resource and has been used in the semi-arid population for fauna purposes, including food and medicines, representing an important source of minerals, bioactive compounds and fibers. The objective of this study was to evaluate in vitro the practical effects of the xique-xique juice (denominated XJ) against several probiotic strains of Lactobacillus, one to mention L. acidophillus LA-05, L. casei L-26 and L. paracasei L- The total number of viable cells from the Lactobacillus strains was monitored in Mann, Rogosa and Sharpe (MRS) broth, containing 1% XJ (10 g/L-1 ) and XJ 2% (20 g/L-1 ), glucose (20 g/L 1 ) and fructo-oligosaccharides - FOS (20 g/L-1 ) for a period of 48 h. In addition, the evidence was conditioned to the metabolic activity of probiotic strains when culture forms were cultivated, such as pH, bacterial production and sugar consumption. For each Lactobacillus strain tested, similar concentrations of viable cells were observed in different culture media, ranging between 8.3 - 9.0 log CFU/mL and pH values ranging from 3.5 to 3.8, except for broths containing SX, which between 5.4 and 5.9 at the end of the 48h culture. The cultivation of all strains of Lactobacillus in MRS with glucose, FOS or XJ, the production of organic acids (acid acetic, malic, succinic and lactic) and the consumption of sugars (glucose, fructose and maltose) over time incubation, binding to high bacterial metabolic activity. In general, all tested Lactobacillus strains have similar capacity to ferment FOS and XJ, although some quantities have been related to sugar production and sugars consumption have been detected. Another way to make XJ present a prebiotic potential against Lactobacillus strains was observed. The results obtained can add value to the development and utilization of this cactus, providing an insertion of a new product for a food industry, as well as potential use as a carbon source in the culture media.